Increase of protein and antioxidant activity of orito banana silage. Technical note - Caicedo, W.; Diáfara, Derwin; Pérez, M.; Ferreira, F. N. A.; Pico, Karla; Cachago, Kely; Valle, S.; Ferreira, W. M. (Cuban Journal of Agricultural Science, 2020)
In order to determine protein content, total phenols and antioxidant activity of green orito banana (Musa acuminata AA) fruit silage, inoculated with whey, for its use as animal feeding, a completely randomized design was implemented, with six treatments (ensiling time): 0, 1, 4, 8, 15 and 30 days. The best results (P <0.05) for crude protein were obtained on days 4 (15.54%), 8 (15.44%), 15 (15.41%) and 30 (15.33%). Total phenols showed their best results on day 30 (35,812.85 μMol GAE/kg DM) and antioxidant activity on day 15 (3,034.98 μMol TROLOX/kg DM). It is concluded that, through fermentation process of the waste green orito banana fruit, between 0 and 30 days, the best protein content and antioxidant activity were achieved at 15 days, which resulted in a food with potential for animal health. Key words: antioxidants, solid fermentation, residue fruit, microbial protein